2021
DOI: 10.1016/j.dcn.2021.100934
|View full text |Cite
|
Sign up to set email alerts
|

The influence of monetary reward on proactive and reactive control in adolescent males

Abstract: Highlights Reward reduced RT interference during reactive control, but increased RT interference during proactive control in male adolescents. Increased reward-related cue-locked theta power was associated with increased RT interference on proactive trials. Increased reward-related stimulus-locked theta inter-channel phase synchrony was related to facilitated performance on proactive trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…As expected, we observed increases in theta ICPS, but similar to the pattern of results for ITPS, we did not observe age‐related changes in theta ICPS. In one of the few developmental studies of stimulus‐related ICPS, no age‐related changes in theta ICPS were reported across adolescence (Bowers et al., 2021). On the other hand, we found a strong delta ICPS response to errors when compared to correct responses in young children, suggesting that delta phase synchrony between frontocentral and frontolateral areas may play an important role in error processing in young children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, we observed increases in theta ICPS, but similar to the pattern of results for ITPS, we did not observe age‐related changes in theta ICPS. In one of the few developmental studies of stimulus‐related ICPS, no age‐related changes in theta ICPS were reported across adolescence (Bowers et al., 2021). On the other hand, we found a strong delta ICPS response to errors when compared to correct responses in young children, suggesting that delta phase synchrony between frontocentral and frontolateral areas may play an important role in error processing in young children.…”
Section: Discussionmentioning
confidence: 99%
“…The task consisted of 75% Go trials and 25% No‐Go trials. As in previous studies involving RT‐based tasks with children (Bowers et al., 2021; Morales et al., 2016), all Go and No‐Go data were cleaned to remove anticipatory responses (RTs < 150 ms) prior to the computation of accuracy measures. Response accuracy was calculated on both Go and No‐Go trials.…”
Section: Methodsmentioning
confidence: 99%
“…The rationale behind this interpretation is that brain areas communicate with each other by using synchronized neural oscillations ( Fries et al, 2005 , Singer, 1999 ). Developmental researchers have used this measure to examine the connectivity in the Mu (alpha) band between visual areas and motor areas to study infant’s processing of others’ actions ( Debnath et al, 2019 ) as well as connectivity between medial prefrontal cortex and lateral prefrontal cortex to study cognitive control ( Bowers et al, 2021 , Buzzell et al, 2019 ).…”
Section: Computing Tf Analysesmentioning
confidence: 99%
“…Next, we will illustrate the output of our TF processing scripts with TF surface plots and topographic plots from a study of reward’s influence on cognitive control in adolescent males using a rewarded cued flanker paradigm ( Bowers et al, 2021 ). For the purposes of this illustration, we will focus on stimulus-locked data from incongruent stimuli in 25 male children (Mean age = 10.55, SD = 1.10, Range = 9.08 −13.92).…”
Section: Examplesmentioning
confidence: 99%
See 1 more Smart Citation